Design and simulation of a UOIT copper–chlorine cycle for hydrogen production - Orhan, Mehmet Fatih (2012)
A design and simulation study of the four-step copper–chlorine (Cu–Cl) cycle using Aspen Plus software (Aspen Technology Inc., Cambridge, MA)is reported. The simulation consists of four main sections: hydrolysis, oxy-decomposition, electrolysis, and drying. This paper explains and justifies how the actual reaction kinetics is factored into these four main sections. Also, it illustrates all the process units that are used in the simulation of four-step Cu–Cl cycle, providing their associated specifications and design parameters. It is found that hydrolysis reactors with smaller capacities and larger (≥10/1) steam to CuCl ratios were desirable to increase the reaction efficiency and prevent the formation of side products such as CuO and CuC. In contrast, larger capacity oxy-decomposition reactors with longer residence times are preferable to allow enough time for the copper oxychloride to decompose. Therefore, 10 (or more) small-scale hydrolysis reactors can feed one oxy-decomposition reactor with large capacity to keep continuity of the flow in the overall cycle. On the basis of the process flow sheet, a pinch analysis is developed for an integrated heat exchange network to enable effective heat recovery within the Cu–Cl cycle.